Sheridan, America - Readings In Themes And Eras - Adomanis, James (Teaching History: A Journal of Methods, 1993)
"Although the selections in this text were made for historic value and topical significance, (Mary S. Sheridan notes that she] also tried to choose materials that I enjoyed and found interesting." In hopes of setting a theme and a tone for America: Readings in Themes and Eras, the editor quotes from Ralph Waldo Emerson's The American Scholar: "The Literature of the poor, the feelings of the child, the philosophy of the street, the meaning of household life, are topics of the time. . . . I ask not for the great, the remote, the romantic; . . . . I embrace the common, I explore and sit at the feet of the familiar, the low. Give me insight into to-day, and you may have the antique and future worlds."